Revision of genus Acrozangis Breddin (Hemiptera: Pentatomidae: Pentatominae) with description of a new species from India - Salini, S.; Schmidt, C. (Zootaxa, 2018)
The genus Acrozangis Breddin, 1900 is revised from India, with description of a new species, Acrozangis dakshinae sp. nov. from southern India. As the holotype female specimen of the type species of Acrozangis, Acrozangis semiprasina Breddin, 1900, is destroyed, the male specimen assigned to A. semiprasina by Breddin (1900) has been designated as the neotype. Though Acrozangis superficially resembles the genera Cuspicona or Glaucias, the very distinct morphological characters such as the resting of the apex of basal abdominal tubercle on a groove of the posterior apex of sternal carina or in other words the apex of basal abdominal tubercle concealed by the posterior apex of metasternal carina and well developed mesosternal carina, lamellate anteriorly and not surpassing forecoxae make this genus unique. A. semiprasina Breddin, 1900 and C. antica Vollenhoven, 1868 were found to be subjective synonyms. The species C. antica Vollenhoven, 1868 is not congeneric to species of Cuspicona Dallas and hence transferred from Cuspicona to Acrozangis and proposed A. antica comb. nov. A lectotype for Cuspicona antica Vollenhoven, 1868 is also designated. A. semiprasina is proposed as a new synonymy to A. antica. The morphological characters support the placement of A. antica in the tribe Nezarini rather than in the Rhynchocorini (where Cuspicona is placed) are discussed.